2020
DOI: 10.5056/jnm19062
|View full text |Cite
|
Sign up to set email alerts
|

Mosapride Improves Lower Esophageal Sphincter and Esophageal Body Function in Patients With Minor Disorders of Esophageal Peristalsis

Abstract: Background/Aims High-resolution manometry (HRM) has broadened the awareness of minor esophageal peristaltic disorders. However, the treatments for these minor disorders are limited and the role of prokinetics has been controversial. This study evaluates the effect of mosapride in patients with minor peristaltic disorders. Methods This study prospectively enrolled 21 patients with esophageal symptoms who were diagnosed with minor peristaltic disorders by gastroscopy and HRM using the Chicago classification vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“… 8 , 10 , 11 A recent meta-analysis study including 16 randomized control trials reported that PPIs with prokinetics showed a significant reduction in global GERD symptoms regardless of the prokinetic type, refractoriness, or ethnicity compared to PPI monotherapy (risk ratio of reflux symptoms resolution, 1.22; 95% confidence interval, 1.11 to 1.35; P < 0.0001). 12 Mosapride improved esophageal symptoms and significantly enhanced distal contractile integral in a study by Kim et al 13 The medical approach should be determined by the patient’s symptoms. However, it seems that medication may be considered if symptoms are present.…”
mentioning
confidence: 98%
“… 8 , 10 , 11 A recent meta-analysis study including 16 randomized control trials reported that PPIs with prokinetics showed a significant reduction in global GERD symptoms regardless of the prokinetic type, refractoriness, or ethnicity compared to PPI monotherapy (risk ratio of reflux symptoms resolution, 1.22; 95% confidence interval, 1.11 to 1.35; P < 0.0001). 12 Mosapride improved esophageal symptoms and significantly enhanced distal contractile integral in a study by Kim et al 13 The medical approach should be determined by the patient’s symptoms. However, it seems that medication may be considered if symptoms are present.…”
mentioning
confidence: 98%